Evidence against a Pleistocene desert refugium in the Lower Colorado River Basin. (7th June 2014) - Holmgren, Camille A.; Betancourt, Julio L.; Peñalba, M. Cristina; Delgadillo, José; Zuravnsky, Kristin; Hunter, Kimberly L.; Rylander, Kate A.; Weiss, Jeremy L.; Riddle, Brett
Abstract Aim The absence of Sonoran Desert plants in late Pleistocene‐aged packrat middens has led to speculation that they survived glacial episodes either in refugia as intact associations (Clementsian community concept) or in dry microsites within chaparral or woodland according to individualistic species responses (Gleasonian community concept). To test these hypotheses, we developed a midden record from one likely refugium in north‐eastern Baja California, Mexico. We also measured stomatal guard cell size in fossil leaves to further evaluate site‐level individualistic responses of Larrea tridentata (creosote bush) ploidy races to climatic changes, including monsoonal history, over the late Quaternary. Location Sierra Juárez, Lower Colorado River Basin, north‐eastern Baja California, Mexico. Methods Packrat (Neotoma) middens were collected from ˂ 300 m elevation on the eastern piedmont of the Sierra Juárez. Plant macrofossils and pollen were analysed from 50 dated middens, including determination of Larrea tridentata ploidy races. Results Pleistocene middens dating back to > 55, 000 cal. yr bp contained a mix of extralocal species characteristic of chaparral and pinyon–juniper–oak woodland, along with some modern desert elements. Many other desert taxa were absent during the Pleistocene, although most had arrived by the beginning of the Holocene 11, 700 years ago. Main conclusions The assemblage of chaparral, woodland and select desert elements refutes the hypothesis that the Lower Colorado River Basin served as a late Pleistocene refugium for Sonoran Desert flora. The rapid arrival of most missing desert species by the early Holocene suggests they did not have far to migrate. They probably survived the last glacial period as smaller, disparate populations in dry microsites within chaparral and pinyon–juniper–oak woodlands. Diploid and tetraploid races of Larrea tridentata were present during the Pleistocene, but hexaploids did not appear until the mid‐Holocene. This demonstrates that individualistic responses to climate involved genetic variants, in this case cytotypes, and not just species.